Diagnostic Value of Immune-Related Genes in Kawasaki Disease - Liu, Dong; Song, Meixuan; Jing, Fengchuan; Liu, Bin; Yi, Qijian (Frontiers in Genetics, 2021)
Kawasaki disease (KD) is a systemic vasculitis that predominantly damages medium and small-sized vessels, mainly causes coronary artery lesions(CALs). The diagnostic criterion of KD mainly depends on clinical features, so children are easy to suffer from missed diagnosis and CALs. Through analysis, a total of 14 immune-related DEGs were obtained, of which IL1B, ADM, PDGFC and TGFA were identified as diagnostic markers of KD. Compared with non-KD group, KD patients contained a higher proportion of naive B cells, activated memory CD4 T cells, gamma delta T cells and neutrophils, while the proportions of memory B cells, CD8 T cells, activated memory CD4 T cells and activated NK cells were relatively lower. In conclusion, Immune-related genes can be used as diagnostic markers of KD, the difference in immune cells between KD and non-KD might provide new insight in understanding the pathogenesis of KD.